A systematic review, meta-analysis and meta-regression of the effect of protein supplementation on resistance training-induced gains in muscle mass and strength in healthy adults - Morton, R. W.; Murphy, K. T.; McKellar, S. R.; Schoenfeld, B. J.; Henselmans, M.; Helms, E.; Aragon, A. A.; Devries, M. C.; Banfield, L.; Krieger, J. W.; Phillips, S. M. (British Journal of Sports Medicine, 2018)
Objective: We performed a systematic review, meta-analysis and meta-regression to determine if dietary protein supplementation augments resistance exercise training (RET)-induced gains in muscle mass and strength. Data sources: A systematic search of Medline, Embase, CINAHL and SportDiscus. Eligibility criteria: Only randomised controlled trials with RET =6 weeks in duration and dietary protein supplementation. Design: Random-effects meta-analyses and meta-regressions with four a priori determined covariates. Two-phase break point analysis was used to determine the relationship between total protein intake and changes in fat-free mass (FFM). Results: Data from 49 studies with 1863 participants showed that dietary protein supplementation significantly (all p<0.05) increased changes (means (95% CI)) in: strength—one-repetition-maximum (2.49 kg (0.64, 4.33)), FFM (0.30 kg (0.09, 0.52)) and muscle size—muscle fibre cross-sectional area (CSA; 310 µm2 (51, 570)) and mid-femur CSA (7.2 mm2 (0.20, 14.30)) during periods of prolonged RET. The impact of protein supplementation on gains in FFM was reduced with increasing age (-0.01 kg (-0.02,-0.00), p=0.002) and was more effective in resistance-trained individuals (0.75 kg (0.09, 1.40), p=0.03). Protein supplementation beyond total protein intakes of 1.62 g/kg/day resulted in no further RET-induced gains in FFM. Summary/conclusion: Dietary protein supplementation significantly enhanced changes in muscle strength and size during prolonged RET in healthy adults. Increasing age reduces and training experience increases the efficacy of protein supplementation during RET. With protein supplementation, protein intakes at amounts greater than ~1.6 g/kg/day do not further contribute RET-induced gains in FFM.